No Detectable Electroencephalographic Activity After Clinical Declaration of Death Among Tibetan Buddhist Meditators in Apparent Tukdam, a Putative Postmortem Meditation State - Lott, Dylan T.; Yeshi, Tenzin; Norchung, N.; Dolma, Sonam; Tsering, Nyima; Jinpa, Ngawang; Woser, Tenzin; Dorjee, Kunsang; Desel, Tenzin; Fitch, Dan; Finley, Anna J.; Goldman, Robin; et al. (Frontiers in Psychology, 2021)
Recent EEG studies on the early postmortem interval that suggest the persistence of electrophysiological coherence and connectivity in the brain of animals and humans reinforce the need for further investigation of the relationship between the brain’s activity and the dying process. Neuroscience is now in a position to empirically evaluate the extended process of dying and more specifically, to investigate the possibility of brain activity following the cessation of cardiac and respiratory function. Under the direction of the Center for Healthy Minds at the University of Wisconsin-Madison, research was conducted in India on a postmortem meditative state cultivated by some Tibetan Buddhist practitioners in which decomposition is putatively delayed. For all healthy baseline (HB) and post-mortem (PM) subjects presented here, we collected resting state electroencephalographic data, Mismatch Negativity (MMN), and Auditory Brainstem Response (ABR). In this study, we demonstrate the feasibility that a sparse electrode EEG configuration is capable of capturing well-defined ERP waveforms from living subjects under very challenging field conditions. While living subjects displayed well-defined MMN and ABR responses, no recognizable EEG waveforms were discernable in any of these tukdam cases.